Effect of self‐management intervention on prognosis of patients with chronic heart failure: A meta‐analysis - Chunqian Feng; Yanmei Wang; Shuang Li; Zhi Qu; Shanqing Zheng (Wiley, 2023)
Abstract Aim The purpose of this study is to explore the influence of self‐management intervention on four prognostic indicators of readmission rate, mortality rate, self‐management ability and quality of life in patients with chronic heart failure. Design A meta‐analysis. Methods This study was selected from the related studies published from January 1999 to January 2022, and was searched by searching five databases: PubMed, Science of Website, China National Knowledge Infrastructure (CNKI), Wan Fang and Wei Pu (VIP). All standardized randomized controlled trial studies were collected, and the quality evaluation and meta‐analysis of the included literature were conducted. Results This study included 20 randomized controlled trials involving 3459 patients with chronic heart failure. Meta‐analysis results showed that self‐management intervention could reduce the readmission rate of patients with chronic heart failure, improved self‐management ability of patients, improved quality of life, but there was no statistical significance in mortality.